A cross sectional study on knowledge, attitude, practice regarding emergency contraception - Putchakayala, Jahnavi; Rao, Manjula; Edwards, Prashanthy; Mohan, Mini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency contraception (EC) is the contraception administered to a woman after unprotected intercourse. This study aims to assess the knowledge, attitude, practice of emergency contraception among patients of 15-45 years attending Obstetrics and Gynaecology outpatient department. Methods: A cross sectional study was conducted in Durgabai Deshmukh Hospital, Hyderabad during June 2014 to June 2016. This study included 300 women. A pre structured questionnaire was employed after obtaining informed written valid consent from the patient and institutional ethical committee clearance. Data on age, socio economic status, education, religion, marital status, their knowledge, attitude, practice regarding emergency contraception was obtained, tabulated and analysed using chi-square test. Results: Out of 300 women, 52% belong to 15-25 years, 31% belong to 26-35 years, 17% belong to 36-45 years. 21.6% of the study population heard of EC. Among these 51% heard from media, 24% from friends, 25% from medical personnel. 18.6% of the study population knew the correct time frame of use, knew that is not an abortion pill, effective in preventing pregnancy, could not prevent the spread of sexually transmitted diseases. 85% of the study population have positive attitude. 14.6% of the population practiced EC. Out of them 88% have used emergency contraceptive pills, 12% have used Intra uterine contraceptive device. 77% got EC over the counter, 23% got through prescription. Conclusions: The study highlights the need to motivate women for effective and appropriate use of emergency contraception when required and arrest the trend towards unwanted pregnancy.